DNA damage, inflammation and aging: Insights from mice - Arvanitaki, Ermioni S.; Stratigi, Kalliopi; Garinis, George A. (Frontiers in Aging, 2022)
Persistent DNA lesions build up with aging activating inflammation, the body’s first line of immune defense strategy against foreign pathogens and irritants. Once established, DNA damage-driven inflammation takes on a momentum of its own, due to the amplification and feedback loops of the immune system leading to cellular malfunction, tissue degenerative changes and metabolic complications. Here, we discuss the use of murine models with inborn defects in genome maintenance and the DNA damage response for understanding how irreparable DNA lesions are functionally linked to innate immune signaling highlighting their relevance for developing novel therapeutic strategies against the premature onset of aging-associated diseases.